Respostas

2013-11-20T17:07:27-02:00
7) 
a)x=y+3  substitui x na outra equação         b)x=3y substitui x na outra equação
2(y+3) +y=9                                                3y-y=2
2y+6+y=9                                                     y=2/2
y=6/3                                                            y=1  e x=3
y=2  e  x=5

c)x= 10+y substitui x na outra equação
2( 10+y)-y=8
20+2y-y=8
y=8-20
y=-12 e  x=-2


18)
a) x=2y  substitui x na outra equação
3( 2y) +5y=55
6y+5y=55
y=55/11
y=5 e x=10

1 5 1
muuuuito obrigada Marianesilva21b
:)